Efficacy of adjuvant intrastromal and combination of intrastromal and intracameral voriconazole in Aspergillus fumigatus-induced moderate fungal keratitis in rabbits (Medical Journal of Indonesia, 2021)
BACKGROUND There is no in vivo evidence for the effectiveness of adjuvant intrastromal and combination of intrastromal and intracameral voriconazole (VCZ) for treating Aspergillus fumigatus keratitis. This study aimed to compare the efficacy of both agents against it. METHODS A randomized, masked, controlled experimental study was conducted on 11 albino New Zealand white rabbits in which moderate fungal keratitis was induced by inoculating spores of A. fumigatus to the cornea. The rabbits were allocated into 3 groups: 50 μg/0.1 ml intrastromal VCZ injection, 50 μg/0.1 ml intrastromal VCZ and intracameral VCZ injections, and topical VCZ (control). The treatment was given 5 days after inoculation. Epithelial defect, infiltrate size, corneal ulcer depth, and hypopyon were evaluated clinically. Histopathological and mycological examinations were also done 14 days after treatment. RESULTS All rabbits in the adjuvant treatment groups demonstrated a tendency of a better clinical response with decreasing size of epithelial defect (p = 0.679) and infiltrate (p = 0.755) than in the control group. Direct microscopy, corneal culture, and chop corneal tissue culture were still positive in most of the rabbits from all groups. Histopathological examination showed an increase of inflammatory cells after treatment in all groups, especially in rabbits which were inoculated with A. fumigatus spores in both eyes. CONCLUSIONS An adjuvant combination of intrastromal and intracameral VCZ showed a tendency of better clinical response for A. fumigatus-induced moderate fungal keratitis in rabbits.